The Role of BMT NU Service Performance to Increase Customer Loyalty from a Sharia Perspective - Misroji Misroji; Faiz Faiz; Muhammad Zainuddin Sunarto (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study aims to analyze the role of BMT NU service performance to increase customer loyalty from a Sharia perspective, focusing on factors such as customer satisfaction, emotional and spiritual support, and compliance with Sharia principles. The research method involved in-depth interviews with 30 customers and 10 BMT managers, as well as observations of ongoing service interactions. The results showed that 85% of customers were satisfied with the quality of service provided, and 78% of them stated that their positive experiences contributed to their loyalty to BMT. The implementation of responsive and ethical services, as well as attention to customer needs, resulted in positive interactions that increased customer trust and satisfaction. The findings also showed that emotional and spiritual support played an important role in strengthening the relationship between BMT and customers, with 70% of respondents reporting that such support made them feel more connected. Despite challenges in maintaining consistent service performance, this study concluded that BMT NU can increase customer loyalty by strengthening service performance that focuses on quality, transparency, and fairness.